2018
DOI: 10.1155/2018/3873179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Temperatures on the Moisture Migration and Microstructure of Beef

Abstract: e e ects of freezing temperature on the microstructure and moisture migration of beef were investigated, aiming to provide the potential theoretical basis for the beef storage. Drip loss, surface hydrophobicity, and secondary structure of myo brillar proteins, ice crystal, and micro-and ultrastructure of meat were analyzed at 4°C, −1°C, −6°C, −9°C, −12°C, and −18°C, respectively. Results indicated that the drip loss and surface hydrophobicity of samples stored at −12°C were signi cantly lower than that stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Significant decreases in relaxation time and population of immobilized water were also observed in salmon and yellowfin tuna during 0 and 4 °C storage . The progressive decrease in the immobilized water relaxation time could be explained by the shrinkage of muscle fiber of beef during storage, which has been reported in a previous publication . When myofibrils shrink, the strain within the myofibril increases, and water can remain in the myofiber or diffuse into the interstitium.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Significant decreases in relaxation time and population of immobilized water were also observed in salmon and yellowfin tuna during 0 and 4 °C storage . The progressive decrease in the immobilized water relaxation time could be explained by the shrinkage of muscle fiber of beef during storage, which has been reported in a previous publication . When myofibrils shrink, the strain within the myofibril increases, and water can remain in the myofiber or diffuse into the interstitium.…”
Section: Resultssupporting
confidence: 72%
“…From Fig. (b), it is obvious that the gap between the muscle bundles increased from 0 to 10 days due to shrinkage of muscle fibers as well as the fracture and separation of exomysium . The above results illustrate that the microstructure of beef muscle was seriously damaged during refrigeration storage, which might be responsible for the loss in WHC, and changes in water mobility and distribution.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Results indicated that throughout the freezing process, the muscle fiber structure of the −40 °C and −60 °C groups were consistently more dense than those of the −18 °C treatment, a finding which was consistent with Kaale et al [ 16 ] who reported formation of small crystals at a lower temperature that were evenly distributed both inside and outside the cells, leading to less damage to the tissue. Li et al [ 11 ] confirmed that beef samples stored at lower temperatures were more compact, ensuring better water-holding capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Utrera et al [ 10 ] compared the effects of freezing temperatures (−8 °C, −18 °C, and −80 °C) and concluded that frozen storage had a significant effect on TBARS values in beef patties, with −80 °C having the strongest inhibitory effect on lipid oxidation. Li et al [ 11 ] asserted that lower freezing temperatures could effectively reduce the denaturation of beef protein. Moreover, Lee et al [ 12 ] reported that the shelf life of frozen beef products gradually decreased as the frozen temperature increased (−5 °C, −15 °C, and −23 °C).…”
Section: Introductionmentioning
confidence: 99%